Pengaruh Debt To Equity Ratio dan Return On Aset terhadap Underpricing dengan Ukuran Perusahaan sebagai Variabel Moderasi - Bindaru Abudani (Jurnal Literasi Akuntansi, 2024)
Purpose: This research aims to prove the influence of debt to equity ratio and return on asset on underpricing with firm size as a moderation variable.Method: This research uses quantitative methods by collecting data from the Indonesia Stock Exchange (idx.co.id) and financial reports of companies experiencing underpricing in 2016-2022. The sample was selected using purposive sampling, with the criteria of companies experiencing underpricing, publishing complete financial reports, using the rupiah currency, and making a profit during the 2016-2023 period. Data analysis includes descriptive analysis, classical assumption testing, and multiple linear regression analysis with hypothesis testing.Finding: The research results show that the debt to equity ratio has a positive effect on underpricing, while the return on asset has a negative effect on underpricing. In addition, it was found that company size can strengthen the influence of debt to equity ratio and return on asset on underpricing.Novelty: Researcher added firm size as a moderating variable to find out whether firm size can make other factors such as debt to equity ratio and return on asset have a stronger or weaker effect on underpricing.